2019
DOI: 10.1186/s40902-019-0201-9
|View full text |Cite
|
Sign up to set email alerts
|

Botulinum toxin-A injection into the anterior belly of the digastric muscle for the prevention of post-operative open bite in class II malocclusions: a case report and literature review

Abstract: Background Class II malocclusion patients with hyperdivergent facial types are characterized by short mandibular body lengths and anterior open bite. Accordingly, the treatment for hyperdivergent skeletal class II malocclusion is a lengthening of the mandibular body length and a counterclockwise rotation of the mandible. To prevent post-operative relapse, botulinum toxin-A (BTX-A) injection can be a retention modality. Case presentation A class II open-bite patient rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Clinical applications of BTX-A In three of the included studies [10,18,27], patients received BTX-A injection into the ABDM muscle as an adjunctive therapy for orthognathic and trauma surgery, in order to prevent postoperative relapse. It is known that skeletal stability following mandibular advancement is a controversial topic in the literature, with various factors being implicated in postoperative relapse [28].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Clinical applications of BTX-A In three of the included studies [10,18,27], patients received BTX-A injection into the ABDM muscle as an adjunctive therapy for orthognathic and trauma surgery, in order to prevent postoperative relapse. It is known that skeletal stability following mandibular advancement is a controversial topic in the literature, with various factors being implicated in postoperative relapse [28].…”
Section: Discussionmentioning
confidence: 99%
“…As BTX-A injections induce muscular weakness, some authors showed that BTX-A injection into the ABDM can correct an open bite caused by a bilateral mandibular angle fracture [10]. A single dose of BTX-A injection into the ABDM can be a useful method in preventing surgical relapse in patients with deep-bite and open-bite malocclusion, treated with orthognathic surgery [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to its aesthetic function, the toxin can also be used functionally in other muscles to reduce muscle tension in the postoperative phase, prevent fracture or displacement of the fixation material, 6 and reduce the likelihood of recurrences caused by muscle hyperactivity. 7 , 8 …”
Section: Discussionmentioning
confidence: 99%
“…Osteofixation was achieved by absorbable PLLA, which demonstrated predictable skeletal stability compared to that of titanium plating systems [14]. Immediately after the orthognathic procedure, we injected routine dosage of botulinum toxin into the masseter muscles bilaterally to decrease the muscular force [15]. In the surgical change, point B was significantly moved superiorly in the CA group but not in the SFA group, although maxillary impaction had been performed.…”
Section: Discussionmentioning
confidence: 99%